Β-Glucosidase improve the aroma of the tea infusion made from a spray-dried Oolong tea instant. (1st April 2022) - Jiang, Qing-xiang; Li, Li-jun; Chen, Feng; Rong, Bo; Ni, Hui; Zheng, Fu-ping
Abstract: The β-glucosidase treatment was investigated to improve the aroma of the infusion made from a spray-dried instant Oolong tea (SIOT) comparing with the infusion of the freeze-dried instant Oolong tea (FIOT). The quantitative descriptive analysis showed that the overall aroma acceptability of the SIOT infusion with β-glucosidase treatment (GSIOT) and FIOT infusion were significantly higher than that of SIOT infusion ( P < 0.05). Multiple linear regression analysis showed that the intensities of floral, grassy and sweet notes were positively correlated with the overall aroma acceptability. The total contents of volatile compounds and odour active values (OAVs) in GSIOT infusion (contents: 93989.8 μg/L; OAVs: 7285.2) were the highest, followed by FIOT infusion (contents: 35882.6 μg/L; OAVs: 6495.6) and SIOT infusion (contents: 16090.4 μg/L; OAVs: 1980.1). The OAVs analysis, aroma reconstruction and omission test showed that the increases in benzyl alcohol, geraniol, ( Z )-3-hexen-1-ol, methyl salicylate and ( E )- β -damascenone were the major contributors to the aroma improvements resulting from the β-glucosidase treatment. This study indicates a reference for yielding high-quality tea beverages with spray-dried instant teas. Graphical abstract: Image 1 Highlights: β-Glucosidase could improve the aroma of spray-dried instant Oolong tea. Spray-dried instant Oolong tea with β-glucosidase treatments have aromas close to freeze-dried counterparts. The intensity of floral, grassy, sweet notes is positively correlated with the overall aroma acceptability of instant tea. Benzyl alcohol, geraniol, ( Z )-3-hexen-1-ol, methyl salicylate, ( E )- β -damascenone are critical in the aroma improvements.